Evaluasi Pengembangan Sistem Informasi Bantuan Pemerintah Pendidikan Kecakapan Kerja - Yulianti, Emi; Yolandan, Fitria; Yohana, Y (STIKOM Tunas Bangsa Pematangsiantar, 2023)
Program Pendidikan Kecakapan Kerja (PKK) is a program that aims to develop work skills in students to suit the needs of the growing industrial world today. The implementation of this program is supported by a Government Assistance Information System that has been operated and developed for 2 years. Evaluation of this system is needed to determine weaknesses and development needs based on user experience. A total of 1,852 users were collected to provide feedback using a Likert scale questionnaire and open-ended questionnaires. The results of the Likert scale questionnaire were processed using a quantitative descriptive approach, while the results of the open-ended questionnaire were processed using a text analysis approach. The results of this study show that user satisfaction is quite high, as it has an acceptability above 85%. The weaknesses that this system still has are the absence of helpdesk and FAQ services, disturbances that are still not resolved quickly, and data integration with NIK which is still often problematic. Based on these shortcomings, the priority recommendations for handling that can be done are to create helpdesk services, FAQ features, and maintenance notifications.